Self-damping of Optical Ground Wire Cables: A Bayesian Approach - Campos, Damián Federico (2023)
The empirical Power Law model has a long usage history in cable self-damping studies, and several types of research have been done to characterize its parameters for various types of cables. In this work, a novel Bayesian model calibration framework is proposed and applied to study self-damping Optical Ground Wire (OPGW) cables. This technique then combines experimental and statistical approaches to obtain the confidence intervals for each parameter and characterize the different regions where the model presents other behaviors. The results enable a better calibration of the model's parameters and agree with the trends already set in the literature. They also provide a new understanding of the model and estimate different uncertainties its application entices